Development of Ethnoscience-Based Physics E-Module Using Kvisoft Flipbook Maker to Improve Students' Science Literacy Skills - Endang Yulyanti; Arif Maftukhin; R. Wakhid Akhdinirwanto (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2022)
Research on the development of an ethnoscience-based physics e-module using the kvisoft flipbook maker was carried out on business and energy materials which aims to determine the feasibility of the e-module in terms of validity, effectiveness, and practicality to improve students' scientific literacy skills. The 4D research model used in this research is (1) define or define, (2) design or design, (3) develop or develop, and (4) disseminate or disseminate. This research was conducted at SMA Negeri 1 Majenang with students of class X MIPA 4 who were used as research subjects in a limited trial totaling six students and a broad trial totaling 30 students. The instruments used in this study were validation sheets, lesson plans implementation sheets, student activity sheets, scientific literacy test sheets, student response questionnaires, and note sheets for learning activities constraints. Data analysis techniques are quantitative, n-gain, and t-test. The results of the study were (1) the validity of the ethnoscience-based physics e-module using the kvisoft flipbook maker was declared valid, (2) the practicality of the ethnoscience-based physics e-module using the kvisoft flipbook maker, which can be seen from the implementation of the lesson plan obtained an average score of 3.77 with categories convenient and the reliability test is 95.3% which is included in the very reliable category, (3) The effectiveness of the ethnoscience-based physics e-module using the kvisoft flipbook maker can be seen from the results of the increase in scientific literacy ability learning outcomes that get an N-gain value of 0.65 which is included in the moderate category, student response questionnaires in the outstanding category, and student activities in the outstanding category. The results of the ethnoscience-based physics module research using the kvisoft flipbook maker were declared feasible to improve students' scientific literacy skills.